Occurrence and aetiology of acute respiratory diseases: results of a longterm surveillance programme - Tůmová, B; Heinz, F; Syrůcek, L; Brůcková, M; Fedová, D; Kunzová, L; Strízová, V (Acta virologica, 1989)
Totals of 58,661,000 acute respiratory disease (ARD) cases, 1,376,651 bronchitis and pneumonia complications, and 93,042 deaths from influenza, bronchitis, pneumonia or chronic pulmonary affection were notified during 11 years of ARD surveillance from 1975 to 1986. All ARD seasons started with the first phase in September-December; this increase in morbidity was caused chiefly by adenoviruses, parainfluenza viruses, rhinoviruses and M. pneumoniae. Second wave of ARD morbidity occurring in January-April used to be explosive and was associated with an influenza epidemic in 9 of the 11 seasons; only in 1978/79 and 1984/85 the ARD epidemics were caused by adenoviruses and especially RSV, the share of influenza being minimal. Pneumonia and bronchitis excesses occured during epidemics caused by M. pneumoniae in 1975/76, 1980/81 and 1985/86. Particularly high mortality excesses occurred in 1976, 1977 and 1983 during epidemics elicited by a new drift variants of influenza A(H3N2). Identification of viral agent of M. pneumoniae attempted in 5474 ARD cases was successful at 37.4%. The respective contributions of parainfluenza viruses, adenoviruses, influenza A virus and RSV to overall aetiologically identified morbidity were 14.2, 13.9, 13.8, and 12.0%. Mixed infections (2-3 agents identified simultaneously) accounted for 14.6% of cases. Type B influenza virus, rhinoviruses, enteroviruses and herpes simplex virus contributed only by 5.6-7.8%. In ordinary seasons the share of M. pneumoniae in aetiologically identified ARD morbidity was 0.6-3.8%; this agent displayed predominance at 5-year cycles, when accounting for 20.5-38.9% of cases. The most frequently detected agents in individual age groups were as follows: in preschool children parainfluenza (18.6%), RSV (16.6%), and adenoviruses (17.4%); in school children M. pneumoniae (26%), influenza A and B (10.2 and 14.7% respectively), and adenoviruses (10.7%); in adolescents and young adults influenza type A (20.2%), M. pneumoniae (15.0%), and rhinoviruses (13.3%); in adults above 25 years age influenza A virus (38%), and other respiratory viruses at a frequency lower than 10% each.
Keywords: Epidemiologic Methods; kuřecí embryo; infekce dýchací soustavy; Czechoslovakia; Infant; virové nemoci; předškolní dítě; Humans; Československo; zvířata; Disease Outbreaks; roční období; Virus Diseases; Pneumonia, Mycoplasma; Age Factors; epidemiologické metody; Child, Preschool; Adolescent; Seasons; Respiratory Tract Infections; Chick Embryo; epidemický výskyt choroby; věkové faktory; Animals; lidé; mladiství; dítě; Child; kojenec; mykoplazmová pneumonie